Stress intensity factors for embedded cracks within torsionally loaded square prismatic bars / Zhou Ding - Zhou, Ding (2017)
Solid bars are widely used in engineering applications for machine components and structures. Since the presence of an embedded crack in a solid bar could lead to a catastrophic failure of a whole structure, relevant studies on evaluating quantitative fracture values are always sought for the improvement of design in components. Due to the complexity of the experimental setup for evaluating an embedded crack in a solid component, numerical modelling becomes an attractive solution. Up to this date, only few studies of evaluating the stress intensity factors for the embedded cracks in a solid bar are reported in literature. Therefore, this research focuses on the evaluation of the stress intensity factors (SIFs) of an elliptical embedded crack in a square prismatic metallic bar subjected to torsion loading. To this end, the effects of various crack parameters on SIFs are investigated: crack aspect ratio, crack inclination and crack eccentricity. A software package of the boundary element method (DBEM) named BEASY is utilized to perform the analyses. J-integral method is adopted in order to compute the SIFs. Results show that as the crack aspect ratio increases, the absolute value of K2 increases while K3 decreases. Moreover, by evaluating 8 eccentricity values, it is found that K2 and K3 increases with the crack eccentricity. Through numerical analysis, it is revealed that for the case of inclined crack, the inclination angle of 45 degree produces maximum value of K1. Finally, the numerical findings are related to the stress distribution in the cross section of square bar using the theory of elasticity.